Outcome and management of invasive candidiasis following oesophageal perforation. Issue 2 (24th August 2012) - Hoffmann, Martin; Kujath, Peter; Vogt, Florian‐M.; Laubert, Tilman; Limmer, Stefan; Mulrooney, Thomas; Bruch, Hans‐Peter; Jungbluth, Thomas; Schloericke, Erik
Summary The regular colonisation of the oesophagus with a Candida species can, after oesophageal perforation, result in a contamination of the mediastinum and the pleura with a Candida species. A patient cohort of 80 patients with oesophageal perforation between 1986 and 2010 was analysed retrospectively. The most common sources with positive results for Candida were mediastinal biopsies and broncho‐alveolar secretions. Candida species were detected in 30% of the patients. The mortality rate was 41% in patients with positive microbiology results for Candida, whereas it was 23% in the remaining patient cohort. This difference did not reach statistical significance (P = 0.124). Mortality associated with oesophageal perforation was attributed mainly to septic complications, such as mediastinitis and severe pneumonia. During the study period we observed a shift towards non‐albicans species that were less susceptible or resistant to fluconazole. In selected patients with risk factors as immunosuppression, granulocytopenia and long‐term intensive‐care treatment together with the finding of Candida, an antimycotic therapy should be started. A surgical approach offers the possibility to obtain deep tissue biopsies. The antimycotic therapy should start with an echinocandin, as the resistance to fluconazole is growing and to cover non‐albicans Candida species, too.